Effect of delayed auditory feedback on stuttering with and without central auditory processing disorders - Picoloto, Luana Altran [UNESP]; Cardoso, Ana Cláudia Vieira [UNESP]; Cerqueira, Amanda Venuti [UNESP]; de Oliveira, Cristiane Moço Canhetti [UNESP] (FapUNIFESP (SciELO), 2017)
Purpose: To verify the effect of delayed auditory feedback on speech fluency of individuals who stutter with and without central auditory processing disorders. Methods: The participants were twenty individuals with stuttering from 7 to 17 years old and were divided into two groups: Stuttering Group with Auditory Processing Disorders (SGAPD): 10 individuals with central auditory processing disorders, and Stuttering Group (SG): 10 individuals without central auditory processing disorders. Procedures were: fluency assessment with non-altered auditory feedback (NAF) and delayed auditory feedback (DAF), assessment of the stuttering severity and central auditory processing (CAP). Phono Tools software was used to cause a delay of 100 milliseconds in the auditory feedback. The Wilcoxon Signal Post test was used in the intragroup analysis and Mann-Whitney test in the intergroup analysis. Results: The DAF caused a statistically significant reduction in SG: in the frequency score of stuttering-like disfluencies in the analysis of the Stuttering Severity Instrument, in the amount of blocks and repetitions of monosyllabic words, and in the frequency of stuttering-like disfluencies of duration. Delayed auditory feedback did not cause statistically significant effects on SGAPD fluency, individuals with stuttering with auditory processing disorders. Conclusion: The effect of delayed auditory feedback in speech fluency of individuals who stutter was different in individuals of both groups, because there was an improvement in fluency only in individuals without auditory processing disorder.
Keywords: Feedback; Hearing; Language and hearing; Sciences; Speech; Speech disorders; Stuttering